Safety and efficacy of 2% chlorhexidine gluconate aqueous versus 2% chlorhexidine gluconate in 70% isopropyl alcohol for skin disinfection prior to percutaneous central venous catheter insertion in preterm neonates: the ARCTIC randomised-controlled feasibility trial protocol. Issue 2 (8th February 2019) - Clarke, Paul; Craig, Jean V; Wain, John; Tremlett, Catherine; Linsell, Louise; Bowler, Ursula; Juszczak, Ed; Heath, Paul T
Abstract : Introduction: Catheter-related sepsis is one of the most dangerous complications of neonatal intensive care and is associated with significant morbidity and mortality. Use of catheter-care 'bundles' has reduced the incidence of catheter-related sepsis, although individual components have not been well studied. Better evidence is needed to guide selection of the most appropriate antiseptic solution for skin disinfection in preterm neonates. This study will inform the feasibility and design of the first randomised controlled trial to examine the safety and efficacy of alcohol-based versus aqueous-based chlorhexidine antiseptic formulations for skin disinfection prior to percutaneous central venous catheterisation in preterm neonates. The antiseptics to be compared are 2% chlorhexidine gluconate (CHG) aqueous and 2% CHG in 70% isopropyl alcohol. Methods and analysis: The Antiseptic Randomised Controlled Trial for Insertion of Catheters (ARCTIC) is a two-centre randomised-controlled feasibility trial. At least 100 preterm infants born at <34 weeks' gestation and due to undergo percutaneous insertion of a central venous catheter will be randomly allocated to receive prior skin disinfection with one of the two antiseptic solutions. Outcomes include: i) recruitment and retention rates; ii) completeness of data collection; iii) numbers of enrolled infants meeting case definitions for definite catheter-related sepsis, catheter-associated sepsis and catheter colonisation and iv) safety outcomes of skin morbidity scores recorded daily from catheter insertion until 48 hours post removal. The key feasibility metrics will be reported as proportions with 95% CIs. Estimated prevalence of catheter colonisation will allow calculation of sample size for the large-scale trial. The data will inform whether it will be feasible to progress to a large-scale trial. Ethics and dissemination: ARCTIC has been approved by the National Health Service Health Research Authority National Research Ethics Service Committee East of England (Cambridge South) (IRAS ID 163868), was adopted onto the National Institute of Health Research Clinical Research Network portfolio (CPMS ID 19899) and is registered with an International Standard Randomised Control Trials Number (ISRCTN: 82571474; Pre-results) and European Clinical Trials Database number 2015-000874-36. Dissemination plans include presentations at scientific conferences, scientific publications and sharing of the findings with parents via the support of Bliss baby charity. Trial registration number: ISRCTN82571474 ; Pre-results.